Journalists’ attitude towards maternal health education broadcast on radio in Oyo State, Nigeria (2011)
The study investigated journalists’ attitude towards maternal health education (MHE) broadcast on radio in Oyo State, Nigeria. One hundred journalists were surveyed randomly from the federal, state and privately owned radio stations in Oyo state. Data were collected using structured questionnaires and analysed using frequency distribution, percentage, chi-square and t-test. Results showed that majority (54%) were males and within the age of 29- 30 years. They all have formal education with majority (72%) having work experience more than 5 years. Knowledge of maternal health was high (65%) and (52%) had favourable disposition to MHE. Constraints faced by journalist were lack of sponsors and lack of funds. Inferential statistics revealed that education (/2 = 9.55, p< 0.005), radio stations ownership (x = 16.45, P<0.005) and programmes aired (%= 0.20, p<0.005) were significantly related to journalists’ attitude to MHE broadcast on radio. Similarly, significant difference (t = 29.15, p<0.005) exist between male and female journalists’ attitude to MHE broadcast on radio. Proper education, gender main streaming and adequate funding are panacea to MHE broadcast on radio.